Таня Гроттер и посох волхвов: [повесть] / Дмитрий Емец - Емец Дмитрий Александрович (Таня Гроттер, 2016)
Экземпляры: ф.6 (20250116) / Инвентарный номер: 4326 И / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Е 60 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445